2014
DOI: 10.12681/mms.398
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocapsa japonica (Raphidophyceae) occurrence and ecological features within the phytoplankton assemblage of a cyclonic eddy, offshore the Eastern Alboran Sea.

Abstract: The Raphidophycean Fibrocapsa japonica Toriumi & Takano was detected for the first time offshore in the Eastern Alboran Sea (Western Mediterranean) in October 2006. Its distribution appeared very localised and atypical, as it was abundant only in the open waters of a cyclonic eddy. Microscope counts of the natural phytoplankton assemblages revealed that F. japonica was dominant in the microplankton, together with Dinophyceae, within and below the cyclonic nutrient-rich dome (25 - 30 m). Bacillariophyceae w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(61 reference statements)
1
3
0
Order By: Relevance
“…On a large scale, the variability of Chl-a concentration in the AB is known to be driven by the inflow of nutrient-rich Atlantic waters that enter the Alboran Sea through the Gibraltar strait (Taupier-Letage and Millot, 1988) and progress eastwards along the AB. The same conclusions have also been drawn more recently by several authors (Fani et al, 2014;Huertas et al, 2012;Lazzari et al, 2012;Pasqueron de Fommervault et al, 2015). Consequently, the eastward propagating eddies modulate the circulation of water masses beyond the continental shelf (Pessini et al, 2020), generating intense vertical mixing (Millot et al, 1990).…”
Section: Seasonal Variabilitysupporting
confidence: 76%
See 2 more Smart Citations
“…On a large scale, the variability of Chl-a concentration in the AB is known to be driven by the inflow of nutrient-rich Atlantic waters that enter the Alboran Sea through the Gibraltar strait (Taupier-Letage and Millot, 1988) and progress eastwards along the AB. The same conclusions have also been drawn more recently by several authors (Fani et al, 2014;Huertas et al, 2012;Lazzari et al, 2012;Pasqueron de Fommervault et al, 2015). Consequently, the eastward propagating eddies modulate the circulation of water masses beyond the continental shelf (Pessini et al, 2020), generating intense vertical mixing (Millot et al, 1990).…”
Section: Seasonal Variabilitysupporting
confidence: 76%
“…It generally follows the continental slope and generates small eddies of 10-100 km diameter, lasting a few weeks or months. Periodically, this current forms a growing meander of 50-100 km; it can detach to form an anticyclonic eddy of 100-200 km diameter that encompasses the entire thickness of the Med water (El-Geziry and Bryden, 2010;Fani et al, 2014;Millot, 1989). Some oceanic eddies persist for up to three years, circulating in the AB in a cyclonic circuit (Millot and Taupier-Letage, 2005).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Increased phytoplankton levels may also occur in coastal areas, especially near large river mouths, due to the nutrients available in the water. In addition to this, harmful algal blooms have been detected in many coastal areas, producing problems for human health and activities [Penna et al, 2007]; these blooms have been also observed in offshore mesoscale eddies, representing a 'seed bank' for further dispersion and spreading of the harmful species [Fani et al, 2014]. The red box in Figure 1 delimits a subarea which is currently considered to correspond to that of the MOMAR project, although the study area of respective Project was actually slightly smaller and centered on the Ligurian Sea.…”
Section: Study Areamentioning
confidence: 99%